ANALYSIS OF DETERMINANTS OF THE HUMAN DEVELOPMENT INDEX ON THE ISLAND OF SULAWESI (2010-2022) - Mahmut, Cici; Nurhuda, Nurhuda; Amrullah, Nursinah (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2023)
This research aims to analyze the factors that influence the Human Development Index (HDI) on Sulawesi Island in 2010-2022. This research uses multiple regression analysis with the Human Development Index as the dependent variable, while the open unemployment rate, poverty and capital expenditure as independent variables. The data source in this research is secondary data in the form of data on the open unemployment rate, the number of poor people and the realization of capital expenditure. The results of this research show that the open unemployment rate variable and the capital expenditure variable have a positive and significant effect on the Human Development Index variable on Sulawesi Island in 2010-2022. Meanwhile, the poverty variable shows that the results have a negative and significant effect on the Human Development Index variable on Sulawesi Island in 2010-2022. It is hoped that the government of each province on the island of Sulawesi can create policies that are more effective in increasing the human development index in their regions, namely reducing the level of open unemployment by creating more job opportunities, so that the number of poor people decreases and can get better education and health facilities. Good. Furthermore, the government of each province on Sulawesi Island is expected to be able to utilize all the resources it has in order to have maximum regional income and be able to realize each regional budget appropriately and effectively in order to accelerate the development of their respective regions.